2015
DOI: 10.1002/pits.21821
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Distress and the Role of Experiential Avoidance

Abstract: Teachers’ psychological wellbeing is important for teachers and students, but is highly stressful, particularly in special education. We examined the role of experiential avoidance (EA) in the wellbeing of 529 middle and elementary school teachers. EA involves the tendency to avoid thoughts, feelings, and other internal experiences even when doing so causes long-range consequences. Using a teacher-specific measure, we investigated its relationship to stress associated with student misbehavior and limited socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 64 publications
(85 reference statements)
3
29
0
4
Order By: Relevance
“…The authors found that 25.13% of their sample of grammar school teachers exceeded the clinical cut-off 16. The highest proportion of teachers (approximately 24%) showed conspicuities on the scale ‘emotional tiredness’, which was also reported in another study 9 16. Moreover, a further study revealed that student teachers reported even higher rates of ‘emotional tiredness’ than did qualified teachers 17…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The authors found that 25.13% of their sample of grammar school teachers exceeded the clinical cut-off 16. The highest proportion of teachers (approximately 24%) showed conspicuities on the scale ‘emotional tiredness’, which was also reported in another study 9 16. Moreover, a further study revealed that student teachers reported even higher rates of ‘emotional tiredness’ than did qualified teachers 17…”
Section: Introductionsupporting
confidence: 76%
“…Experiential avoidance is the tendency to avoid internal experiences like thoughts and feelings even if doing so causes negative consequences. The authors found that experiential avoidance correlated with depression and burnout symptoms, and that it mediated the relationship between external stressors and personal well-being 9. Schmitz et al found that excessive self-demands at the beginning of the teaching career are a risk factor for later invalidity 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding stress, it is proven that it is a predictive variable, coinciding with the stress model [1] and with further studies [3,34,52,53]. It is necessary to learn to use the most functional coping strategies and to manage emotions and stress [25,26,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Research into burnout has shown a high prevalence in teachers [1][2][3], who are one of the professional groups most prone to suffer from it [4,5]. There is generally a broad consensus characterizing burnout as a syndrome in which three groups of symptoms are present: Emotional exhaustion, depersonalization, and reduced personal accomplishment at work [6].…”
Section: Introductionmentioning
confidence: 99%